O-band mode-locked praseodymium-doped fluoride fiber laser using nickel phosphorus trisulfide. (May 2023) - Ahmad, H.; Nizamani, B.; Azam, A.D.; Samion, M.Z.; Yasin, M.; Sun, S.
Highlights: Generation of mode-locked pulses using an all-fiber setup in the O-band region. The mode-locked laser had a center wavelength of 1302.3 nm. Performance of NiPS3 as a saturable absorber was investigated. Ultrashort pulse width of 370 fs was obtained with a peak power of 46.2 kW. Abstract: In this work, we demonstrated a mode-locked fiber laser operating in the O-band region using nickel phosphorus trisulfide (NiPS3 ) as a saturable absorber (SA) for the first time. An arc-shaped fiber was coated with a layer of NiPS3 to serve as the SA which was then integrated into a praseodymium (Pr 3+ )-doped fluoride fiber laser (PDFFL) cavity for signal emission at 1.3 µm. The mode-locked laser operates at a center wavelength of 1302.3 nm, around the zero-dispersion wavelength. The mode-locked PDFFL has a repetition rate and signal-to-noise ratio (SNR) of 0.403 MHz and 55 dB, respectively. Ultrashort pulses of 370 fs were generated using the NiPS3 -SA with a pulse energy of 17.1 nJ and a peak power of 46.2 kW. The NiPS3 -SA in our work has shown the potential of this 2D nanomaterial ability to generate mode-locked pulses at 1.3 µm, which was rarely explored.